2014
DOI: 10.1126/science.1244512
|View full text |Cite
|
Sign up to set email alerts
|

Btk29A Promotes Wnt4 Signaling in the Niche to Terminate Germ Cell Proliferation in Drosophila

Abstract: Btk29A is the Drosophila ortholog of the mammalian Bruton's tyrosine kinase (Btk), mutations of which in humans cause a heritable immunodeficiency disease. Btk29A mutations stabilized the proliferating cystoblast fate, leading to an ovarian tumor. This phenotype was rescued by overexpression of wild-type Btk29A and phenocopied by the interference of Wnt4-β-catenin signaling or its putative downstream nuclear protein Piwi in somatic escort cells. Btk29A and mammalian Btk directly phosphorylated tyrosine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 25 publications
5
56
3
Order By: Relevance
“…Several constituents of ECs are known to be involved in silencing BMP ligands and facilitators. These include molecules necessary for regulating the cellular processes that contact germline cells (as exemplified by Rho; Kirilly et al, 2011), EGFR (Liu et al, 2010), Wnt pathway components (Hamada-Kawaguchi et al, 2014;Luo et al, 2015;Wang et al, 2015;Mottier-Pavie et al, 2016), Piwi (Ma et al, 2014) and multiple regulators of chromatin modifications (Eliazer et al, 2011;Wang et al, 2011;Xuan et al, 2013;Maimon et al, 2014). Here, we report that the Hh and Hpo/Yki pathways also serve to suppress BMP ligand production in ECs.…”
Section: Discussionmentioning
confidence: 79%
“…Several constituents of ECs are known to be involved in silencing BMP ligands and facilitators. These include molecules necessary for regulating the cellular processes that contact germline cells (as exemplified by Rho; Kirilly et al, 2011), EGFR (Liu et al, 2010), Wnt pathway components (Hamada-Kawaguchi et al, 2014;Luo et al, 2015;Wang et al, 2015;Mottier-Pavie et al, 2016), Piwi (Ma et al, 2014) and multiple regulators of chromatin modifications (Eliazer et al, 2011;Wang et al, 2011;Xuan et al, 2013;Maimon et al, 2014). Here, we report that the Hh and Hpo/Yki pathways also serve to suppress BMP ligand production in ECs.…”
Section: Discussionmentioning
confidence: 79%
“…It has been well documented that the BMP/Dpp signaling derived from niche CpCs locally suppresses GSC differentiation by silencing bam transcription in GSCs [7,10]. Recent studies identified several factors as niche regulators in ECs that control GSC/CB differentiation [42][43][44]. However, fate determination between stem cell self-renewal and differentiation must be under strict control to ensure proper development and tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt9a is more closely related to Drosophila DWnt4 than to other members of the WNT family in mammals (Bergstein et al 1997). DWnt4 is expressed in the somatic escort cells and promotes the passage from proliferation to germ cell differentiation via expression of RNA-binding protein Piwi by DCtnnb1 in Drosophila (Hamada-Kawaguchi et al 2014). The Piwi-interacting RNA pathway plays important roles in silencing of repeat elements through repressive histone modifications (Sienski et al 2012).…”
Section: Rspo1mentioning
confidence: 98%